2007
DOI: 10.1097/01.tp.0000264998.23349.54
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21: An Interleukin-2 Dependent Player in Rejection Processes

Abstract: IL-21 is a critical cytokine for IL-2 dependent immune processes. Blockade of the IL-21 pathway may provide a new perspective for the treatment of allogeneic responses in patients after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…MAPK signaling is the key in T cell development and activation (32) and acts as an upstream activator of NFAT (27Y30). Thus, by inhibition of the MAPK pathway, CNIs suppress the proliferation and function of T cells (35,36), which are prominent players in the cascade of alloreactivity leading to graft rejection (37,38). The proof that MAPK monitoring has clinical utility should come from a study that correlates this biomarker with the occurrence of rejection.…”
Section: Discussionmentioning
confidence: 95%
“…MAPK signaling is the key in T cell development and activation (32) and acts as an upstream activator of NFAT (27Y30). Thus, by inhibition of the MAPK pathway, CNIs suppress the proliferation and function of T cells (35,36), which are prominent players in the cascade of alloreactivity leading to graft rejection (37,38). The proof that MAPK monitoring has clinical utility should come from a study that correlates this biomarker with the occurrence of rejection.…”
Section: Discussionmentioning
confidence: 95%
“…IL-21 plays an important role in a number of autoimmune diseases (Vogelzang and King 2008;Spolski et al 2008). IL-21 R alpha-chain increases were noted in the human heart during acute rejection (Baan et al 2007). Thus increased presence of IL-21 R may mediate myocardial cell damage in some autoimmune diseases (Vogelzang and King 2008;Spolski et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…This is especially the case in the heart where knowledge of the effect of interleukins on the heart is variable as it has been studied intensively for some interleukins and hardly at all for others. Nevertheless, data suggest that interleukins are involved in mediating myocardial cell damage in some infectious (Fonseca et al 2007) and autoimmune diseases (Vogelzang and King 2008;Spolski et al 2008), reductions in cardiac contractility (Cao et al 2003;Tio et al 2000) and the immune response in cardiac transplantation (Baan et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…IL-21 expression by T cells was up-regulated via IL-2 in a mixed lymphocyte reaction. In the same experiment, IL-21 functioned as a co-stimulator for IL-2 to augment T cell proliferation and cytotoxicity (Baan et al 2007). …”
Section: Introductionmentioning
confidence: 95%
“…The present knowledge on the role of the IL-21/IL-21R system in allografts is limited. Recently, Baan et al (2007) reported a strong upregulation of the IL-21 and IL-21R mRNA in biopsies of human heart transplants during acute rejection. IL-21 expression by T cells was up-regulated via IL-2 in a mixed lymphocyte reaction.…”
Section: Introductionmentioning
confidence: 99%